The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4314/njt.v36i2.41
|View full text |Cite
|
Sign up to set email alerts
|

Design and determination of the efficiency of a slanting-type solar water distillation kit

Abstract: The solar water distillation system is a non-toxic and promising device for water purification. A slanting-type solar water distillation kit was fabricated and tested outdoor under the meteorological conditions of Imo State University, Owerri, Nigeria. The system consists of four major components; a wooden basin of surface area 0.16 m 2 , an absorber surface, a slanting glass roof and a condensate channel. Locally available materials were used to fabricate the solar still. The solar still produced an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The graphs also justify that the temperature difference (that is, the difference between the glass cover and absorber plate temperatures) is the major factor responsible for evaporation. This trend was also observed by several authors (Ahsan et al, 2013;Ali et al, 2019;Edeoja et al, 2015;Kumar and Bai, 2008;Murugavel et al, 2010;Onyegegbu, 1986;Ozuomba et al, 2017;Sathyamurthy et al, 2015). Preheating the feed water to the solar still basin plays an important role in increasing the productivity of the still (Ahmadi et al, 2017;Badran and Abu-khader, 2007;Delgado-Torres et al, 2007;Kalogirou et al, 2016).…”
Section: Solar Radiation and Temperature Variations In Solar Stillsupporting
confidence: 69%
“…The graphs also justify that the temperature difference (that is, the difference between the glass cover and absorber plate temperatures) is the major factor responsible for evaporation. This trend was also observed by several authors (Ahsan et al, 2013;Ali et al, 2019;Edeoja et al, 2015;Kumar and Bai, 2008;Murugavel et al, 2010;Onyegegbu, 1986;Ozuomba et al, 2017;Sathyamurthy et al, 2015). Preheating the feed water to the solar still basin plays an important role in increasing the productivity of the still (Ahmadi et al, 2017;Badran and Abu-khader, 2007;Delgado-Torres et al, 2007;Kalogirou et al, 2016).…”
Section: Solar Radiation and Temperature Variations In Solar Stillsupporting
confidence: 69%
“…The paper [6] was carried out to analyze the temperature difference between the inner and outer glass covers of conventional basin type solar stills and low thermal inertia solar stills obtained by modifying conventional stills, and it was found that for conventional stills, the maximum temperature difference was up to 7.14 % during the day and significant in the morning and evening, then for low thermal inertia, the difference is greater up to 10.2 %. Then in the paper [7] which was a study that used a tilt type solar-powered water distillation tool, this distillation tool was analyzed so that it was found that the tool could produce an average of 0.09 m 3 of water per day.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The system recorded a distillation efficiency of 36.8%. Ozuomba et al [10] fabricated and tested a solar distillation kit in Owerri. The system recorded a mean daily production of 0.09m 3 for an absorber area of 0.16m 2 .…”
Section: Conventional Solar Still Was First Introduced By Charlesmentioning
confidence: 99%